Pengaruh Kualitas Pelayanan Kunjungan Online terhadap Kepuasan Warga Binaan di Lembaga Pemasyarakatan Perempuan Kelas III Manokwari - Syarifuddin, Sitti Aetika; Hafel, Muhlis; Purwanto, Purwanto (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study aims to examine the impact of online visitation service quality on the satisfaction of inmates at the Class III Women's Penitentiary in Manokwari. The background of this research highlights the importance of inmate rehabilitation programs based on the correctional system to develop well-rounded individuals, as stipulated by Law PAS-14.OT.02.02 of 2014 on Correctional Service Standards. Ensuring the rights of inmates, including visitation services, is essential for their well-being and reintegration. This quantitative study utilized a sample of 47 respondents. Data analysis was performed using multiple linear regression analysis, partial tests, and coefficient of determination tests. The findings indicate that the quality of online visitation services significantly influences inmate satisfaction. The study concludes by underscoring the necessity of enhancing visitation service quality to improve inmate satisfaction and support their reintegration process into society as responsible and productive members.